Dual-sensitive fluorescent nanoprobes for detection of matrix metalloproteinases and low pH in a 3D tumor microenvironment. Issue 28 (30th June 2022) - Rainu, Simran; Parameswaran, Sowmya; Krishnakumar, Subramanian; Singh, Neetu
Abstract : pH/MMP-9 sensitive fluorescent nanoprobes as non-invasive imaging tool for distinguishing tumor-like microenvironments (low pH and upregulated MMP-9) from non-cancerous microenvironments in 3D microscaffolds. Abstract : The overexpression of matrix metalloproteinases and low extracellular pH are two key physiological parameters involved in cancer initiation, progression, and metastasis. These have been the targets for several cancer detection and imaging modalities. Here, dual-sensitive nanoprobes have been fabricated from carbon nanoparticles decorated with a MMP-9 sensitive peptide sequence. Carbon nanoparticles are known for their intrinsic fluorescence properties and hence used as a pH-sensing moiety in the nanoprobes. In addition to this, selective-cleavage of the peptide sequence by MMP-9 results in the generation of a fluorescence signal due to separation of the quencher molecule from the fluorophore attached onto the MMP-9 sensitive peptide sequence, resulting in its detection. This protease-specific activation of the nanoprobes helps in precise tumor environment detection and imaging. The nanoprobes were thoroughly characterized for their chemical, physical and biological activities. The potential of these dual-sensitive nanoprobes to distinguish tumor-like microenvironments (low pH and elevated MMP-9 levels) from non-cancerous ones was evaluated in vitro in 2D cell culture as well as in 3D microscaffolds. The fluorescence microscopy images obtained in both in vitro systems revealed that low pH and high MMP-9 levels could be successfully visualised using these dual-sensitive nanoprobes. Therefore, these nanoprobes would find potential applications as a non-invasive imaging tool for visualising tumor margins in real-time.